2013
DOI: 10.1111/are.12166
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the dietary biotin on zebrafishDanio rerioreproduction

Abstract: An experiment was conducted to investigate the effects of dietary biotin on zebrafish Danio rerio reproduction. Biotin and avidin (biotin antagonist) were added to two isonitrogenous and isocaloric purified diets to provide molar avidin:biotin ratios of 0:1 (biotin‐sufficient diet) and 120:0 (biotin‐unsufficient diet). Each diet was fed to a group of males mean initial mass 0.262 g) and a group of females (mean initial mass 0.285 g) for 99 days. Following this feeding period, males fed biotin‐sufficient diet e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Recently, Yossa et al (2013b) found lower gonado-somatic index, sperm density, sperm motility and lower sperm viability in biotin-deficient zebrafish. In addition, in the presence of a biotin-sufficient male zebrafish, the biotin-sufficient female spawned 12 times more eggs than the biotin-deficient female, while in the presence of the biotin-deficient males, both biotin-deficient and biotin-sufficient females spawned a substantial lower number of eggs, although biotin-sufficient females still produced 5 times more eggs than the biotin-deficient females (Yossa et al 2013b). This result suggests that the spawning efficiency of the female zebrafish is influenced by the fitness or biotin status of the male which courts the female for spawning (Yossa et al 2013b).…”
Section: Biotin In Cell Cycle and Reproductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recently, Yossa et al (2013b) found lower gonado-somatic index, sperm density, sperm motility and lower sperm viability in biotin-deficient zebrafish. In addition, in the presence of a biotin-sufficient male zebrafish, the biotin-sufficient female spawned 12 times more eggs than the biotin-deficient female, while in the presence of the biotin-deficient males, both biotin-deficient and biotin-sufficient females spawned a substantial lower number of eggs, although biotin-sufficient females still produced 5 times more eggs than the biotin-deficient females (Yossa et al 2013b). This result suggests that the spawning efficiency of the female zebrafish is influenced by the fitness or biotin status of the male which courts the female for spawning (Yossa et al 2013b).…”
Section: Biotin In Cell Cycle and Reproductionmentioning
confidence: 97%
“…This result suggests that the spawning efficiency of the female zebrafish is influenced by the fitness or biotin status of the male which courts the female for spawning (Yossa et al 2013b). Moreover, a higher percentage of visually fertilized eggs was obtained with the biotinsufficient male zebrafish than the biotin-deficient ones, while a higher hatching rate of eggs and larvae survival at 7-day-post-fertilization was obtained with fertilized eggs produced by biotin-sufficient females than biotin-deficient ones (Yossa et al 2013b). To the best of our knowledge, this study for the first time provides evidences of the importance of dietary biotin in fish reproduction, as the biotin status of the male has been demonstrated to be of high importance for successful breeding in zebrafish, because it significantly impacted the reproductive performance of the female.…”
Section: Biotin In Cell Cycle and Reproductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Droney, ; Melo et al, ; Dávila & Aron, ). Other studies have suggested that micronutrients such as carotenoids, amino acids and vitamins can affect ejaculate trait expression (Lederhouse et al, ; Locatello et al, ; Lambrot et al, ; Yossa et al, ; Tomášek et al, ). But we do not know how different dietary components contribute to the variation in ejaculate responses.…”
Section: Introductionmentioning
confidence: 99%
“…The health of laboratory animals is both an animal welfare and a scientific concern, as undernourished, and consequently unhealthy, animals can severely bias experimental results. Use of the zebrafish model system continues to expand across fields, such as aquaculture (Chengfei et al, 2017;Pereira, Carvalho, Cruz, & Saraiva, 2017;Yossa, Sarker, Proulx, & Vandenberg, 2015), making the confounding effects of subpar nutrition increasingly questionable.…”
Section: Introductionmentioning
confidence: 99%